Correção dos aneurismas da aorta torácica e toracoabdominal: técnica de canulação central - Rojas, Salomón Soriano Ordinola (2003)
Introduction: The surgical treatment of the aneurysm of descending thoracic and thoracoabdominal aorta are related with risk of spinal cord ischemic, as well as, coagulation and renal function disorders. Among the spinal cord protection methods, there are liquor drainage, temporary bypass, intercostal arteries implant, deep hypothermia, selective cooling of spinal cord and drugs. Objective: The goal of this paper is to show the viability of using extracorporeal circulation from left atrium to ascending aorta with deep hypotermia for surgical treatment of the thoracic and thoracoabdominal aneurysms. Material and Methods: From January 1994 to July 2001, thirty eight patients were operated, 26 male with mean age of 54.6±12.7. Twelve patients (31.6%) were submitted to correction of thoracoabdominal aneurysm and twenty six to correction of descending aorta aneurysm. The etiologies were: post-trauma in one patient, dilatation after correction of coarctation of the aorta in four patients, syphilitic aortite in two , atherosclerotic in ten patients and aortic dissection in twenty one patients. After extracorporeal circulation installed, the patients were cooled, the faryngeal temperature ranged from 15° and 25°C (20.6±3.2°C). The total circulatory arrest time from nine to thirty six minutes (21.3±6.7). The aortic diameter ranged from 4 to 10.5 cm (8.1±1.5 cm). Results: As neurological complications, paraplegia ocurred in two cases (5.3%) and in one of them there was stroke associated. One patient had paraparesis in inferior members and one, had seizure. The respiratory complications ocurred in twelve (31.6%) patients and tracheostomy was necessary in two cases por delayed ventilaroty support. Two patients from this group (16.7%) died. Two patients had transitory elevation of creatinine but dialysis was not necessary. Emergency operation was performed in two cases and both died. The overall mortality was seven patients (18.4%) and the causes were: bleeding in one patient, respiratory insufficiency in two patients, sudden death in two, heart failure in one and failure of weaning from extracorporeal circulation. Conclusion: Surgical correction of descending thoracic aorta and thoracoabdominal aneurysms during deep hypothermia using extracorporeal circulation with cannulation of left atrium and ascending aorta is a safe method, with low mortality. The complications such as neurologic, respiratory and renal were according to the literature.